429 Racial Disparities Persist Despite Increased Utilization of Deep Brain Stimulation Surgery for Parkinson's Disease. (1st April 2022) - Cramer, Samuel; Do, Truong; Palzer, Elise; Naik, Anant; Rice, Abigail; Novy, Savannah; Hanson, Jacob; Piazza, Amber; Howard, Madeleine; Huling, Jared; Chen, Clark C.; McGovern, Robert A.
Abstract : INTRODUCTION: Deep brain stimulation (DBS) provides improved quality of life for properly selected individuals with Parkinson's disease (PD). Though DBS is a widely accepted and efficacious therapy for PD, significant racial disparities have been reported in the access to DBS, particularly for Black patients. METHODS: The National Inpatient Sample (NIS) was queried to identify PD patients who underwent DBS placement between 2002 and 2018. We examined DBS utilization relative to PD admissions, patient characteristics over time, and whether ACA passage was associated with changes in insurance and DBS utilization among different racial/ethnic groups. RESULTS: In 2014-2018, the odds of PD patients receiving DBS therapy increased 56% compared to 2002-2005 (p < 0.001). In a multivariate logistic regression analysis, the most important factors affecting the likelihood of DBS surgery were race, insurance status and the presence of comorbidities. Black PD patients were 1/5 as likely as White patients to undergo DBS placement (p < 0.001). Individuals with = 2 comorbidities were 20 times less likely to undergo DBS. Patients insured privately compared to those insured by Medicare/Medicaid were 5.22 times as likely to undergo DBS. Passage of the ACA was associated with 2.62 times higher odds of DBS in 2010-2013 for Black PD patients compared to 2002-2005 (p = 0.008). During the period 2014-2018, Black PD patients were 2.33 times more likely to undergo DBS compared to the period 2002-2005 (p = 0.008). CONCLUSION: DBS is increasingly used for healthy, privately insured PD patients. Significant racial disparities persist in the use of DBS for PD despite a modest improvement following passage of the ACA, but prior to most of its implementation, indicating other factors contributed to this change.